Spatial distribution of animal source food consumption and associated factors among children aged 6–23 months in Ethiopia: A geographically weighted regression analysis - Mekuriaw Nibret Aweke; Amare Mesfin; Gebrie Getu Alemu; Berihanu Mengistu; Tewodros Getaneh Alemu; Habtamu Wagnew Abuhay (PLoS ONE, 2025)
Introduction Optimal nutrition during early childhood is essential for growth, cognitive development, and overall health. Animal source foods(ASF) provide essential nutrients like high-quality protein, iron, zinc, calcium, and vitamin B12, which are vital for the physical and cognitive development of young children and to reduce the burden of malnutrition. In Ethiopia malnutrition among children under five remains a significant public health issue. Many children are suffering from chronic and acute undernutrition. This study provides the first spatial analysis of animal source foods consumption among children aged 6–23 months. Objectives The aim of this study is to investigate the spatial distribution of ASF consumption and its associated factors among children aged 6–23 months in Ethiopia using data from the Ethiopia miniDHS 2019. Methodology A cross-sectional study design was used using mini-DHS 2019 data among children aged 6–23 months. Descriptive statistics were used to summarized the study population characteristics and ASF consumption prevalence. Spatial analysis techniques, including Geographical mapping and Moran’s I statistic assessed the spatial distribution of ASF consumption. Geographically weighted regression analyses identified socio-economic, demographic, and geographic factors associated with ASF consumption. Results The study found that 47.7% of Ethiopian children aged 6–23 months consume ASF. Children in regions like Amhara, Tigray, Benishangul-Gumuz, western SNNPR, and Gambela are less likely to consume these foods. Factors linked to higher ASF consumption include mothers with more education, smaller families, households following the Orthodox religion, and wealthier families.. Conclusion and Recommendations According to this study finding animal source food consumption among Ethiopian children aged 6–23 months is relatively low. The finding revealed the significant regional disparities of ASF consumptions. Factors associated with ASF consumption include maternal education, household size, wealth, and religion. Efforts should focus on working to increase maternal education, providing and expansion of family planning services, and increasing affordability of ASF through economic improvement of households. In addition strengthening food supply chains and integrating ASF promotion into healthcare are also essential for improving child nutrition. Interventions in low-consumption areas should address specific local needs to effectively boost ASF consumption and improve child nutrition outcomes.